THE ROLE OF ARTIFICIAL INTELLIGENCE AND ROBOTICS IN MEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article commentates on the concepts of Artificial Intelligence and Robotics. Today, there is talk about the role of Artificial Intelligence and robotics in practices and medicine aimed at improving human health. Their disadvantages are listed, and the advantages are mentioned. As one of the most important areas of medicine, we can see that surgery is also being carried out using modern robotics. It is claimed that these robots are helping surgeons perform difficult surgical procedures more accurately and efficiently.